2022
DOI: 10.1186/s13643-022-02094-0
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to mitigate vaping misinformation: protocol for a scoping review

Abstract: Background The impact of misinformation about vapes’ relative harms compared with smoking may lead to increased tobacco-related burden of disease. To date, no systematic efforts have been made to chart interventions that mitigate vaping-related misinformation. We plan to conduct a scoping review that seeks to fill gaps in the current knowledge of interventions that mitigate vaping-related misinformation. Methods A scoping review focusing on interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…For example, various studies approach interventions on social media alone [3], [4], disregarding other online platforms. In their scoping review on psychological interventions, Gwiaździński, et al [20] reported on development guidelines but did not extract frameworks or report on the characteristics of misinformation. Other scoping reviews focused narrowly on misinformation one health concern, such as HPV [17], vaccine hesitancy [18], COVID-19 [19], and vaping [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, various studies approach interventions on social media alone [3], [4], disregarding other online platforms. In their scoping review on psychological interventions, Gwiaździński, et al [20] reported on development guidelines but did not extract frameworks or report on the characteristics of misinformation. Other scoping reviews focused narrowly on misinformation one health concern, such as HPV [17], vaccine hesitancy [18], COVID-19 [19], and vaping [20].…”
Section: Introductionmentioning
confidence: 99%
“…In their scoping review on psychological interventions, Gwiaździński, et al [20] reported on development guidelines but did not extract frameworks or report on the characteristics of misinformation. Other scoping reviews focused narrowly on misinformation one health concern, such as HPV [17], vaccine hesitancy [18], COVID-19 [19], and vaping [20]. This review aims to take a holistic approach by looking at the theoretical and practical aspects of interventions countering misinformation, namely, conceptual frameworks, population characteristics, misinformation characteristics and practical considerations of design and implementations of interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The recent introduction of alternative forms of nicotine products into the marketplace (e.g., e-cigarettes/vapes, heated tobacco products, and smokeless tobacco) has led to a more complex informational environment. [1][2][3][4] The scientific consensus is that vape aerosol contains fewer numbers and lower levels of toxicants than smoke from combustible tobacco cigarettes. 5 Among youth in the United States, adolescent nicotine vaping use increased from 2017 to 2019 but then started declining in 2020, which includes a decline in daily vaping as well.…”
Section: Introductionmentioning
confidence: 99%
“…The recent introduction of alternative forms of nicotine products into the marketplace (e.g., e‐cigarettes/vapes, heated tobacco products, and smokeless tobacco) has led to a more complex informational environment 1–4 . The scientific consensus is that vape aerosol contains fewer numbers and lower levels of toxicants than smoke from combustible tobacco cigarettes 5 .…”
Section: Introductionmentioning
confidence: 99%